Pneumococcal infection in children with recurrent respiratory diseases - I. V. Babachenko; L. I. Zhelezova; E. A. Kozyrev; E. V. Nikitina; N. S. Tian (Журнал инфектологии, 2024)
In frequently ill children with recurrent respiratory diseases (RRD), violations of local immunity and microbiocenosis of the mucous membranes can contribute to the development of acute and chronic bronchopulmonary diseases. Vaccination against major pathogens, including S. pneumoniae, can help prevent respiratory infections in children.Objective: to study the microbiocenosis and local immunological factors of the nasopharyngeal mucosa in children with RRD, the serotype composition of S. pneumoniae in children with community-acquired pneumococcal pneumonia (CAP) and pneumococcal carriers, as well as the correspondence of the serotype landscape to the composition of modern pneumococcal vaccines.Materials and methods: The study included 150 patients (104 children with RRD and 46 patients with CAP). To assess the condition of the nasopharyngeal mucosa cultural methods, morphofunctional, immunological and capsule PCR typing of S. pneumoniae isolates were performed. Statistical analysis was performed using the Statistica 10.0 package.Results: The age structure was dominated by children aged 3 to 6 years (36%). The majority of patients with RRD had pronounced nasopharyngeal mucosal dysbiosis (n=60), as well as destruction of epithelial cells (n=97). These factors may predispose to the development of bronchopulmonary diseases, including community-acquired pneumonia (CAP). Capsule PCR typing of S. pneumoniae isolates from the nasopharynx was performed in 46 patients. It has been established that in the structure of nasopharyngeal carrier S. pneumoniae in children with CAP, serotypes “3” and 19F prevailed, which were also the main pathogens in pneumococcal CAP. In nasopharyngeal pneumococcal carrier, the thirteen–valent pneumococcal conjugate vaccine (PCV13) overlapped 39.6% (95%CI 27.6–53.1%) of serotypes, in pneumococcal VP – 57.2% (95% CI 36.5-75.5%), while PCV20 overlapped 22.6% more S. pneumoniae serotypes in children with CAP.Conclusion: The strategy for the prevention of acute respiratory infections in children is immunization against pneumococcal infection, which should be carried out taking into account the regional prevalence of S. pneumoniae serotypes.